A qualitative analysis of implementing shared decision making in Child and Adolescent Mental Health Services in the United Kingdom: Stages and facilitators. (January 2016) - Abrines-Jaume, Neus; Midgley, Nick; Hopkins, Katy; Hoffman, Jasmine; Martin, Kate; Law, Duncan; Wolpert, Miranda
Objectives: To explore the implementation of shared decision making (SDM) in Child and Adolescent Mental Health Services (CAMHS), and identify clinician-determined facilitators to SDM.Methods: Professionals from four UK CAMHS tried a range of tools to support SDM. They reflected on their experiences using plan-do-study-act log books. A total of 23 professionals completed 307 logs, which were transcribed and analysed using Framework Analysis in Atlas.Ti.Results: Three states of implementation (apprehension, feeling clunky, and integration) and three aspects of clinician behavior or approach (effort, trust, and flexibility) were identified.Conclusions: Implementation of SDM in CAMHS requires key positive clinician behaviors, including preparedness to put in effort, trust in young people, and use of the approach flexibly.Practice implications: Implementation of SDM in CAMHS is effortful, and while tools may help support SDM, clinicians need to be allowed to use the tools flexibly to allow them to move from a state of apprehension through a sense of feeling "clunky" to integration in practice.